Impact of Age and Gender on the Perceptual Response of Sri Lankan Consumers for different types of Biscuits - Gunathilaka, U. G. S. A; Wijewardhana, U. S; Navaratne, S. B. (International Journal of Food Science and Nutrition, 2019)
The perceptual response of persons in demographic settings is an important deciding factor in consumer food choice. This paper explores the effect of a person’s age and gender on the sensorial response using five types of biscuits such as crackers, sweet biscuits, cream biscuits, savory biscuits and wafers. According to ISO standards, 125 respondents were selected as a consumer panel from a suburban area in Sri Lanka and a sensory analysis was conducted using a five-point hedonic scale. Results were subjected to statistical analysis using IBM SPSS 21.0. Results revealed that there was a positive correlation ship between the age, gender and type of biscuits (P value<0.05). To quantify this relationship, regression analysis was performed for five types of biscuits and the regression equations were developed. According to the study, age and gender are deciding factors in selecting types of biscuits.
Keywords: perceptual response, sensory stimuli, gender, hedonic scale, demographic settings, Biscuits